Finite element analysis of guided wave dispersion in pipes with multichannel acquisition - Le, Ductho; Hoang, Ngoc Quy; Phan, Haidang; Nguyen, Hoai (Vietnam Journal of Mechanics, 2025)
Ultrasonic guided waves have become a key tool in nondestructive evaluation of pipelines, as they can travel long distances with low attenuation while maintaining high sensitivity to defects. Accurate modeling of their dispersion characteristics is essential for inspection design and signal interpretation. This study presents a finite element (FE) framework that advances beyond conventional eigenvalue-based analyses by directly simulating a realistic multichannel acquisition process. A pitch-catch configuration, consisting of a ring actuator and a linear receiver array, is modeled, and dispersion spectra are reconstructed through two-dimensional Fourier transforms—closely mirroring experimental practice. The reconstructed spectra show excellent agreement with analytical solutions, thereby validating the approach. By bridging numerical modeling and experimental acquisition, this FE framework delivers realistic datasets that facilitate advanced signal processing, imaging algorithms, and pipeline inspection strategies.